(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Liver transplantation (LT) is a definitive treatment for end-stage liver disease, acute liver failure, liver tumors, and some metabolic diseases. Re-exploration after surgery is associated with poor clinical outcomes and is considered a quality of care measure. Objective: to determine the frequency and risk factors of reoperation (early relaparotomy) after donor hepatectomy in postoperative LDLT donors. Materials & Methods: A cross-sectional analytical study was conducted at Pir Abdul Qadir Shah Jeelani Institute of Medical Sciences, from December 2023 to May 2024. The study included 672 LDLT donors aged over 18 years. Data on donor age, gender, blood group, operation time, and re-exploration were collected. Primary endpoints were the frequency and causes of re-exploration, and secondary endpoints included the association of re-exploration with clinical outcomes. Statistical analyses were performed using SPSS 25.0, with a significance level set at p < 0.05. Results: The frequency of re-exploration was 2.8%. Among those requiring re-exploration, 42.1% were aged 21-28 years. The difference in re-exploration rate between male and female patients was found to be statistically significant (p<0.001). Blood group analysis revealed 57.9% of re-explored donors had blood group B+. Bleeding was the primary cause of re-exploration in 73.7% of cases. The majority (57.9%) of re-explorations occurred in patients with operation times between 451-550 minutes. Conclusion: This study highlights a relatively low frequency of re-exploration (2.8%) among LDLT donors. However, the significant gender disparity and the high incidence of bleeding as a cause for re-exploration underscore the need for improved postoperative care.